Level set-based topology optimization targeting micropumps employing an induced-charge electro-osmosis flow - Ryuta TANAKA; Kentaro YAJI; Ayami SATO; Kazuhiro IZUI; Takayuki YAMADA; Shinji NISHIWAKI (Nihon Kikai Gakkai ronbunshu, 2016)
The aim of this research is to construct a topology optimization method for the design of micropumps driven by induced-charge electro-osmosis. Micropumps are one of the most important components in micro-fluid devices such as μ-TAS (Micro Total Analysis Systems). In particular, electro-osmotic micropumps offer many advantages. They have a simple structure, are easy to miniaturize, and generate flow that is free from pulsation, but such pumps are typically driven by direct current fields, so electrolysis may cause problems. To avoid the problems of electrolysis, a phenomenon called induced-charge electro-osmosis is attracting increasing attention because, being driven by alternating current fields, electrolysis is much less prevalent. Since the amount of liquid discharge is controlled through the electro-osmotic phenomenon, the micropump performance is greatly influenced by the shapes and locations of the dielectric material in its interior. For the design of the distribution of dielectric material in a micropump, we construct a topology optimization method for the micropump design that maximizes the amount of liquid discharge, using level set boundary expressions so that the expressed structural boundaries are free from expanded grayscale areas. Several numerical examples are provided to confirm the utility of the proposed method.